Risk of paralytic and diarrhetic shellfish poisoning associated with the consumption of bivalves from north Mumbai creek - Shahi, Neetu; Nayak, B B; Mallik, Sumanta Kumar (Indian Journal of Fisheries, 2016)
Risk assessment study with respect to shellfish toxins of algal origin was carried out in coastal villages of Mumbai. LiveMeretrix sp. was collected monthly during November 2005 - December 2006 from Manori creek. Analysis of crude toxins bymouse bioassay (MBA) was done for paralytic shellfish poisoning (PSP) and diarrhetic shellfish poisoning (DSP) and exposureassessment was done by survey in five fishing villages. Level of PSP and DSP toxins were below the detectable limit. Surveyrevealed that 14% had diarrhea, and other stomach related ailments following consumption of clams. Significant number ofPSP causing dinoflagellates Alexandrium minutum, Alexandrium acatenella, Alexandrium tamarense, Gymnodiniumnagasakiense and Pyrodinium bahamense were present in coastal waters. Similarly DSP causing dinoflagellates Dinophysisnorvegica, Dinophysis caudata, Dinophysis rotundata and Dinophysis acuminata were also observed at